Common Ground inconsistencies in dialogue systems: conflict patterns implied by polar question forms - Di Maro, Maria; Origlia, Antonio; Cutugno, Francesco (Dialogue and discourse, 2024)
In linguistics, research on dialogue systems has accentuated the need to focus on various pragmatic aspects for their management and modelling. Among the most important pragma-linguistic speech acts in dialogue systems studies are Clarification Requests, corrective feedback that in some circumstances require access to the set of shared knowledge known as Common Ground. Regarding Common Ground management, pragmatic studies suggest differences in the type of polar questions that people prefer be used in Clarification Requests, where polar questions can have two possible answers: true or false. This preference appears to depend on the relationship between bias and contextual evidence. In this work, we show that varying the form of polar questions in a given pragmatic setting can influence the capability of people to track Common Ground inconsistencies. As a result, we demonstrate that using a negative polar question in Italian has functional consequences when communicating conflicting material in the Common Ground. This can improve the quality of human interactions with dialogue systems, in terms of an improved identification of the conflict. The results obtained in this work provide insights into design of error reporting approaches in natural interactions.